2006
DOI: 10.1007/s11249-006-9167-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of dicationic symmetrical and asymmetrical ionic liquids and their tribological properties as ultrathin films

Abstract: A new series of novel dicationic symmetrical and asymmetrical ionic liquids (ILs) consisting of tributylalkyl phosphonium and alkylimidazolium were synthesized. Their tribological properties in the form of spin-coated ultra-thin films sliding against AISI-52100 steel ball were studied in a ball-on-plate configuration on a Universal Micro-tribometer-2MT tester, using perfluoropolyether (PFPE) and normal ILs as comparisons. The best result is obtained for asymmetrical 1-(1-tributylphosphine-yl-hexyl)-3-methylimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
85
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 34 publications
2
85
1
Order By: Relevance
“…represent a new generation of amphiphilic molecules [16]. The new structures have demonstrated special properties and the potential for use in materials science; for example, in the formation of liquid crystals [17,18], metal coatings [19], and high temperature lubricants [20,21]. Consequently, a deeper knowledge of the aggregation process of dicationic ILs is essential in order to allow the rational design of ILs for specific applications.…”
Section: Introductionmentioning
confidence: 99%
“…represent a new generation of amphiphilic molecules [16]. The new structures have demonstrated special properties and the potential for use in materials science; for example, in the formation of liquid crystals [17,18], metal coatings [19], and high temperature lubricants [20,21]. Consequently, a deeper knowledge of the aggregation process of dicationic ILs is essential in order to allow the rational design of ILs for specific applications.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there are brief reports on the tribological properties of R 4 P-derived RTILs [13,[20][21][22][23][24][25]. In this work, we focused on the relationship between the chemical structure and tribological properties of RT-ILs.…”
Section: Introductionmentioning
confidence: 99%
“…They attributed the excellent tribological properties of these ionic liquid films to their strong adsorptions to the interface and the good transfer film-forming abilities on the counterpart surfaces. Yu et al [19,20] synthesized several kinds of novel ionic liquids and tested their tribological properties as thin films. They found that asymmetrical bis-substituted ionic liquids have the best tribological properties among the tested lubricants, i.e., PFPE, corresponding ionic liquids with single cation, and symmetrical bis-substituted ionic liquids, and the anti-wear life of these films increased with the increment of chain length.…”
Section: Introductionmentioning
confidence: 99%